Relationship between Vitamin D Intake and Bone Density in Elderly Individuals - Muindi, Amos (American Journal of Food Sciences and Nutrition, 2024)
Purpose: The aim of the study was to investigate relationship between vitamin D intake and bone density in elderly individuals. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The relationship between vitamin D intake and bone density in elderly individuals is well-established. Low vitamin D levels are associated with reduced bone density, and supplementation can help improve it, especially in cases of deficiency. The ideal dosage and individual responses vary, and factors like calcium intake, sunlight exposure, and overall health also play a role in maintaining bone density in the elderly. Implications to Theory, Practice and Policy: Calcium homeostasis theory, hormonal regulation theory and bone remodeling theory may be use to anchor future studies on the relationship between vitamin D intake and bone density in elderly individuals. In clinical practice, consider personalized vitamin D supplementation regimens based on individual needs, taking into account factors such as age, gender, dietary habits, and geographical location. Develop evidence-based national or international guidelines for vitamin D intake and supplementation specific to elderly populations.